2010
DOI: 10.1007/s00455-010-9298-9
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Oral Microorgansims and Aspiration Pneumonia in the Institutionalized Elderly: Review and Recommendations

Abstract: Aspiration pneumonia is a leading cause of illness and death in persons who reside in long-term-care facilities and, combined with the lack of proper oral health care and services, the risk of aspiration pneumonia rises. The purpose of this article is to review recent literature on oral hygiene and oral care in long-term-care facilities and report new findings regarding associated risks for aspiration pneumonia, as well as research on oral care and health outcomes. The PubMed MeSH database was utilized to dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
123
0
7

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 160 publications
(142 citation statements)
references
References 44 publications
7
123
0
7
Order By: Relevance
“…Besides hygiene issues in pneumonia and COPD, associations of oral microorganisms and pulmonary infections due to aspiration have been investigated [45]. Usually, aspiration pneumonia is related to lessvirulent bacteria, streptococci and anaerobes that reside in the upper airways or the gastrointestinal tract [45].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides hygiene issues in pneumonia and COPD, associations of oral microorganisms and pulmonary infections due to aspiration have been investigated [45]. Usually, aspiration pneumonia is related to lessvirulent bacteria, streptococci and anaerobes that reside in the upper airways or the gastrointestinal tract [45].…”
Section: Discussionmentioning
confidence: 99%
“…Usually, aspiration pneumonia is related to lessvirulent bacteria, streptococci and anaerobes that reside in the upper airways or the gastrointestinal tract [45].…”
Section: Discussionmentioning
confidence: 99%
“…Individuals with poor oral hygiene have been found to have an increased rate of upper respiratory tract infections, such as pneumonia [5]. Aspiration pneumonia is the second most common infection in elderly in nursing homes, which requires hospital treatment and has the highest mortality [6]. In a study of the risk factors, it was found that a lack of oral hygiene and swallowing difficulties had a significant relationship with pneumonia incidence [7].…”
Section: Introductionmentioning
confidence: 99%
“…In a study of the risk factors, it was found that a lack of oral hygiene and swallowing difficulties had a significant relationship with pneumonia incidence [7]. Frail, elderly people with impaired immune systems may aspirate usually harmless oral micro-flora as candida and these results in opportunistic infections [6]. In the last years lubricating products have been popular as a treatment against oral dryness.…”
Section: Introductionmentioning
confidence: 99%
“…Considerable evidence exists to support an association between dental plaque, poor oral health, and respiratory diseases such as bacterial pneumonia in frail older people, nursing home residents or nosocomial infections in critically ill patients submitted to mechanical ventilation [9][10][11][12]. Teeth or dentures have non-shedding surfaces on which oral biofilms (i.e.…”
Section: Introductionmentioning
confidence: 99%